Avaliação da adequação dos medicamentos prescritos para pacientes idosos internados em hospital de ensino da cidade de Fortaleza - Cunha, Saulo Coelho (2007)
The chronic and degenerative illnesses are common in elderly and frequently many medicines are used to treat them. The prescription medication and the improper use of medicines may lead to undesirable results causing hospital admissions which may be preventable and raising costs in health system. To evaluate the adequacy of drug therapy prescribed to elderly patients admitted in a teaching hospital of Fortaleza city based on Beers and Canadian criteria; to evaluate the adequacy of medicines prescribed in relation to the four of five swedish quality indicators of pharmacotherapy to older patients and to perceive the frequency of adverse drug reactions (ADR) during the hospital stay. This is an observational, descriptive and transversal study by convenience sample. The study was developed in the clinical patients ward of the University Walter Cantidio Hospital from October 2006 and May 2007. Patients 60 years and older admitted in the hospital were included in the study, particularly those that had signed the informed consent previously. A pharmacotherapeutic follow-up sheet with medical records was used taking into account the profile of medicines usage during the hospital stay and the nature of the ADR if this occurred after the hospital admission. The criteria for evaluating the suspected cases of ADR were defined by causality and severity adopted by World Health Organization (WHO) having as technical support the Pharmacovigilance Center of Ceará (CEFACE). The medicines were classified in accordance with the ATC (anatomic-therapeutic-chemical) up to the principal therapeutic group and also were analyzed according to Beers and Canadian criteria and the four Swedish quality indicators of pharmacotherapy to older patients. The software used to analyze the data was the Microsoft Excel 2002 for Windows. The study was approved by the Research Ethics Committee of the University Federal of Ceara. In the set of the 50% patients admitted in the study 42% were men and 58% were women. Half of the elderly were in the range of 60 to 69 years old. Considering the Beers and Canadian criteria, 84% of the patients received inappropriate prescription medication. The study registered 17 medicines potentially inappropriate to elderly persons. Metoclopramide, mineral oil and diazepam were the most frequently prescribed, in this order. In relation to the adverse drug reactions 30% of the patients showed suspected RAM and 69% of those attempted the female sex. The medication class most often implicated with the emergence of ADR was the antithrombotics and the types of ADR most frequent were the gastrointestinal disturbs. In the universe of followed patients a high percentage received inappropriate prescription medication giving evidence of the necessity of a better attendance of prescribing to older patient.